Immunologic, metabolic and genetic impact of diabetes on tuberculosis susceptibility - Ssekamatte, Phillip; Sande, Obondo James; van Crevel, Reinout; Biraro, Irene Andia (Frontiers in Immunology, 2023)
Due to the increasing prevalence of diabetes mellitus (DM) globally, the interaction between DM and major global diseases like tuberculosis (TB) is of great public health significance, with evidence of DM having about a three-fold risk for TB disease. TB defense may be impacted by diabetes-related effects on immunity, metabolism, and gene transcription. An update on the epidemiological aspects of DM and TB, and the recent trends in understanding the DM-associated immunologic, metabolic, and genetic mechanisms of susceptibility to TB will be discussed in this review. This review highlights gaps in the incomplete understanding of the mechanisms that may relate to TB susceptibility in type 2 DM (T2DM). Understanding these three main domains regarding mechanisms of TB susceptibility in T2DM patients can help us build practical treatment plans to lessen the combined burden of the diseases in rampant areas.